Pelatihan Software MathCAD sebagai Penunjang Pembelajaran pada Komunitas Musyawarah Guru Mata Pelajaran Matematika dan Fisika wilayah Gresik, Provinsi Jawa Timur: (MathCAD Software Training as a Learning Support at the Mathematics dan Physics Subject Teachers' Deliberation Community in the Gresik region, East Java Province) - Desita Nur Rachmaniar; Granita Hajar; Abduh Sayid Albana (Prodi Tadris IPA Biologi UIN Mataram, 2024)
Mathematics is a subject that is rarely popular with school students. Difficult material, complicated calculations, dan material that is less interactive when delivered in class are the reasons why this subject is less popular. Technological assistance, such as software, is an important thing to do in order to increase interactive learning. One of the software that is suitable for use as learning support, especially for mathematics dan science subjects, is MathCAD. This MathCAD software can help educators create math problems dan compile exercise books more quickly. The aim of this community service activity is to assist mathematics dan science teachers in teaching dan learning activities, especially in exact subjects. The method used is implementing MathCAD software training for the mathematics dan science teacher communities. With the results obtained from community service activities in the form of MathCAD software training, educators can apply the use of software during the teaching dan learning process, especially mathematics, to make it more interactive.